First Clinical Cases of Spirometrosis in Two Cats in Korea - Kim, Joohyung; Ock, Younsung; Yang, Kihwan; Choe, Seongjun; Park, Kyung-Mee; Lee, Wan-Kyu; Choi, Kyung-Chul; Kim, Soochong; Kwak, Dongmi; Lee, Seung-Hun (Korean journal of parasitology, 2021)
This study reports the first two clinical cases of spirometrosis caused by Spirometra sp. in cats in Korea. In these two cases, the cats vomited, and long proglottids of tapeworm were recovered. The sick cats presented with anorexia and lethargy. However, they unexpectedly showed no diarrhea, which is the main symptom of spirometrosis. Based on a fecal floatation test as well as morphological and molecular analyses, the parasite was diagnosed as Spirometra sp. The 2 cases were treated with praziquantel. This study suggests regular monitoring of health and deworming in companion animals, even when animals are well cared for, with regular preventive medication. Additionally, spirometrosis should be considered in the differential diagnosis in cases of gastrointestinal symptoms in Spirometra endemic areas.